4a²b⁴ - 25x⁶y⁴
(2ab²)² - (5x³y²)²
= (2ab² + 5x³y²)(<span>2ab² - 5x³y²) By difference of two squares</span>
Answer:
x=7 x=-7
Step-by-step explanation:
Solution is attached.
Answer:
See below ~
Step-by-step explanation:
Completing the square :
- 9y² - x - 18y + 10 = 0
- 9y² - 18y + 9 - 9 - x + 10 = 0
- <u>(3y - 3)² - x + 1 = 0</u>
<u></u>
Graph :
Answer:
A and E
Step-by-step explanation:
Answer:
x>1
Step-by-step explanation:
move the constant to the right side and change its sign 7x>10-3
Then subtract the numbers 7x>7
Then divide the inequality by 7 from for both sides.
x>1